The mathematical modelling of liner movement in a magnetic compressor: elastic, liquid and plastic liner models comparison - Galanin, Michail; Lototsky, Aleksey; Rodin, Alexander (Mathematical Modelling and Analysis, 2012)
The paper is aimed to model the electromagnetic acceleration and braking of the liner in magnetic compressor. The 2D approach corresponding to the longitudinal section of spatial region is considered. Liquid, elastic, and plastic models of the liner are presented. The comparative analysis of calculation results for different models and their correlation with experimental data are carried out. The research of the influence of circuit parameters on liner braking is done.